A general synthesis of arylindoles and (1-arylvinyl)carbazoles via a one-pot reaction from N-tosylhydrazones and 2-nitro-haloarenes and their potential application to colon cancer. Issue 88 (18th October 2016) - Bzeih, Tourin; Naret, Timothée; Hachem, Ali; Jaber, Nada; Khalaf, Ali; Bignon, Jerome; Brion, Jean-Daniel; Alami, Mouad; Hamze, Abdallah
Abstract : A synthesis of aryl-indoles, and carbazoles from a one-pot sequence involving the coupling of hydrazones with nitro-haloarenes has been developed. Abstract : A convergent and effective synthesis of 3-aryl-indoles, 2, 3-diaryl indoles, and (1-arylvinyl)carbazoles from a one-pot sequence involving the coupling of N -tosylhydrazones with ortho -nitro-haloarenes followed by a cyclization has been developed. Compound 5i exhibits excellent antiproliferative activity in the low nM range against colon cancer cell lines.